Carrier recombination and transport dynamics in superstrate solar cells analyzed by modeling the intensity modulated photoresponses. Issue 36 (9th September 2019) - Pereyra, Carlos J.; Di Iorio, Yesica; Berruet, Mariana; Vazquez, Marcela; Marotti, Ricardo E.
Abstract : Intensity modulated photovoltage and photocurrent spectroscopy data of CuInS2 solar cells were modeled and fitted with the solution of the continuity equation. Abstract : The dynamics of carrier recombination and transport of two CuInS2 superstrate solar cells was studied by intensity modulated photovoltage and photocurrent spectroscopy (IMVS and IMPS respectively). For the analysis of the resulting data two different approaches were implemented. In the first approach, the typically used analysis in Dye Sensitized Solar Cells (DSSC) was adapted to obtain the characteristic times of the processes involved. The second approach was based on the fittings of both the IMVS and IMPS data to the solution of the continuity equation. These fittings allow the calculation of different dynamic parameters of the cells. Moreover, consistency between the obtained parameters was observed, in good agreement with the typical analysis for DSSC. The resulting dynamics was associated with the presence and distribution of defect states among the samples. Moreover, from the performed analysis, a relation between the results and the post-treatment applied to the solar cells could be established. The difference in the dynamics of the cells is mainly observed in the difference between the electron lifetimes of both solar cells.